A autonomia comunicacional do cibernativo na Internet. - Camboim, Ana Flávia de Luna (2011)
In cyberspace, has been setting a standard of conduct established by the generation born in the era of cyberculture, which we named the cyberneticist. To study the process of building a culture of its own from the communicational autonomy that this internet user develops in cyberspace is our goal. To this end, we conducted a survey exploring the concepts of culture in Santaella (2003), Laraia (2007), Geertz (1989), Jenkins (1998), Girardello (2008) and Capparelli (2002), beyond the culture media and cyberculture in Moreira (2003) and Lemos and Lévy (2010), understanding the interactive media as participatory and cooperative relationship media in the view of Nicolau (2008). We also discuss the invention and the disappearance of childhood (POSTMAN, 1999 and BUCKINGHAM, 2007) and affirmed a new face in the same figure of the cyberneticist. Finally, we classify the types of communicational autonomy manifested by these users: cognitive or thought, expression and production or "autopoietic" (CAPRA, 1996 and 2002), arguing that they and the types of relationships in interactive media can be developed in three classes of environments that are listed and analyzed by us: virtual spaces configured with content for the cyberneticist, virtual spaces with content non-configured for the cyberneticist and virtual spaces with content produced by cyberneticist. As an example of the latter case, we found the content manager called FreeWebs, where are hosted the webshows web video series that use to be fun and require production of a script, soundtrack etc. Throught them, children express their autonomy in the audiovisual language. In this space, where the type of cooperative relationship and the communicational autonomy of production develop, we did seek symbolic standard of the programs and on the content configuration of the sites, noting the existence of a culture of cyberneticist.